2021
DOI: 10.1021/acs.energyfuels.1c01747
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Physical Characteristics of a Pore-Filling Hydrate Reservoir: Particle Shape Effect

Abstract: Methane gas hydrate (MGH) is an important clean energy source. In submarine continental margins, the main hydrate occurrence in the sediment is the pore-filling type, and there is a huge difference in the sediment particle shape. Thus, in this study, with a new algorithm based on X-ray computed tomography (CT), 16 three-dimensional models were reconstructed with different hydrate saturations and particle shapes. Pore network modeling (PNM) was used to characterize the pore space evolution, and the impacts of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The projection data were obtained using InspeXio (Shimazu, Japan) CT scans and reconstructed as two-bit grayscale slices, followed by image noise reduction as well as grayscale correction using median The dimensions of the actual strata in this study were much larger than those of the specimens, so it made more sense to choose REV and observe changes over a region. This method of intercepting REVs was also used in Wu et al 54 and Li et al 55 Figure 1 shows the morphology of NGH under different effective stresses. It can be found that the pore space is gradually compressed with the increase of σ 31 ′.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The projection data were obtained using InspeXio (Shimazu, Japan) CT scans and reconstructed as two-bit grayscale slices, followed by image noise reduction as well as grayscale correction using median The dimensions of the actual strata in this study were much larger than those of the specimens, so it made more sense to choose REV and observe changes over a region. This method of intercepting REVs was also used in Wu et al 54 and Li et al 55 Figure 1 shows the morphology of NGH under different effective stresses. It can be found that the pore space is gradually compressed with the increase of σ 31 ′.…”
Section: Methodsmentioning
confidence: 99%
“…The dimensions of the actual strata in this study were much larger than those of the specimens, so it made more sense to choose REV and observe changes over a region. This method of intercepting REVs was also used in Wu et al and Li et al Figure shows the morphology of NGH under different effective stresses. It can be found that the pore space is gradually compressed with the increase of σ 31 ′.…”
Section: Methodsmentioning
confidence: 99%